Kelp Patch-Specific Characteristics Limit Detection Capability of Rapid Survey Method for Determining Canopy Biomass Using an Unmanned Aerial Vehicle - McPherson, Meredith L.; Kudela, Raphael M. (Frontiers in Environmental Science, 2022)
Kelp forests dominate autotrophic biomass and primary productivity of approximately 30,000 to 60,000 km of shallow temperate and Arctic rocky reef coastline globally and contribute significantly to carbon cycling in the coastal ocean. Rapid biomass turnover is driven by very high growth rates and seasonal environmental drivers. As a result, kelp biomass varies greatly with time, space, and by species. In the northeast Pacific region, bull kelp (Nereocystis leutkeana) and giant kelp (Macrocystis pyrifera) form extensive floating surface canopies with a distinct spectral signature compared to the surrounding water. Studies have shown that remote sensing is advantageous for deriving large-scale estimates of floating surface canopy biomass, which comprises more than 90% of bull and giant kelp standing stock. However, development and validation of remotely derived kelp canopy biomass is lacking because existing approaches are time intensive and costly. This study attempted to close that gap by developing a rapid survey design utilizing diver and unmanned aerial vehicle (UAV) imagery across 6 sites in northern and central California. Kelp sporophytes were collected and measured for morphometric characteristics and genera-specific allometry to canopy biomass. Kelp density was measured using in situ diver surveys and coupled with UAV imagery to quantify kelp canopy biomass at a range of ground sampling distances. We successfully estimated kelp canopy biomass from UAV imagery at 33% (2/6) of the survey sites, but consistently determining canopy biomass via this approach was challenged by both survey design and kelp patch-specific spatial characteristics. The morphologies of bull kelp in Monterey were significantly different than other regions measured, but further work should be conducted to fully characterize differences in canopy biomass at the regional and sub-regional scale. We use this opportunity to suggest survey design strategies that will increase the success of future methodological development of UAV biomass retrieval. We also recommend developing long-term, annual genera-specific monitoring programs across the northeast Pacific region and beyond to validate remote sensing derived biomass estimates beyond the small number of existing well-characterized sites.